2022
DOI: 10.3390/fractalfract6120729
|View full text |Cite
|
Sign up to set email alerts
|

Improved Performance in the Control of DC-DC Three-Phase Power Electronic Converter Using Fractional-Order SMC and Synergetic Controllers and RL-TD3 Agent

Abstract: In this article, starting from a benchmark represented by a Direct Current-to-Direct Current (DC-DC) three-phase power electronic converter used as an interface and interconnection between the grid and a DC microgrid, we compare the performances of a series of control structures—starting with the classical proportional integrator (PI) type and continuing with more advanced ones, such as sliding mode control (SMC), integer-order synergetic, and fractional-order (FO) controllers—in terms of maintaining the const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…The PWM technique employed to control the conventional converter can be adapted for application in MMCs [37]. Different modulation techniques, such as phase disposition modulation, sinusoidal pulse width modulation, carrier phase shift modulation, and nearest level modulation, are commonly employed to control the active devices in MMCs.…”
Section: (4)mentioning
confidence: 99%
“…The PWM technique employed to control the conventional converter can be adapted for application in MMCs [37]. Different modulation techniques, such as phase disposition modulation, sinusoidal pulse width modulation, carrier phase shift modulation, and nearest level modulation, are commonly employed to control the active devices in MMCs.…”
Section: (4)mentioning
confidence: 99%
“…The basis for designing a SC technique is the analytical design of aggregated regulator (ADAR) approach, as described in references [56][57][58]. We will consider a nonlinear dynamical system with n dimensions, governed by the following equation:…”
Section: Sc Designmentioning
confidence: 99%
“…Studies have shown that fractional-order models are superior in characterizing the electrical properties of components in the context of DC-DC converters [9][10][11][12][13]. Applying fractional-order operators to mathematical modeling of DC-DC converters can provide a more comprehensive and accurate description of the electrical characteristics of DC-DC converters [14,15].…”
Section: Introductionmentioning
confidence: 99%